Does Personality Change Follow Deep Brain Stimulation in Parkinson's Disease Patients? - Wilt, Joshua A.; Merner, Amanda R.; Zeigler, Jaclyn; Montpetite, Michelle; Kubu, Cynthia S. (Frontiers in Psychology, 2021)
Deep Brain Stimulation (DBS) has emerged as a safe, effective, and appealing treatment for Parkinson’s Disease (PD), particularly for improving motor symptoms (e.g., tremor, bradykinesia, and rigidity). However, concerns have been raised about whether DBS causes psychological changes, including changes to personality: characteristic and relatively stable patterns of affect, behavior, cognition and desire. In this article, after first presenting some background information about PD and DBS, we examined evidence obtained from various empirical research methods (quantitative, qualitative, mixed methods for evaluating patient valued characteristics) pertaining to whether DBS causes personality change. General limitations across research methods include a lack of randomized clinical trials and small sample sizes. We organized our review of findings according to different layers of personality variables: dispositional traits (including personality pathology), characteristic adaptations, and narrative identity. Though most work has been done on dispositional traits, there is not much evidence that dispositional traits change following DBS. Little work has been done on characteristic adaptations, but there is somewhat consistent evidence for positive perceived progress toward goals across a number of domains: routine activities, work, social/relational, leisure. Nascent work on narrative identity holds promise for revealing issues around self-image that may be common following DBS. We listed a number of strategies for advancing research, highlighting opportunities related to personality conceptualization, personality assessment, and interdisciplinary scholarship. Finally, we offer practical applications of our findings for the informed consent process and for ongoing treatment.